2020
DOI: 10.2478/sgem-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Wall Pressure in Silo with and Without Insert

Abstract: This paper presents a methodology based on the finite element method to simulate the flow of granular materials. Moreover, it allows proper estimation of dynamic pressure during silo discharge since this subject is still under discussion, especially for designing silos with an insert (an input element). A 2-D simulation of the discharge process of a cylindrical silo with cone and a central discharging orifice was performed. Two cases were studied, with and without using insert in silo. Numerical analysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, the storage materials are large numbers of particle aggregates, and their mechanical properties are extremely complex, which is difficult to reasonably estimate using the traditional classical mechanics theory and condensed matter physics theory 12 . In recent years, relevant scholars have found that the maximum dynamic pressure on the silo wall is often several times of the static pressure during silo discharging 13 16 . Thus, if the dynamic pressure on silo wall is not considered during the design process, it will lead to the instability of the silo.…”
Section: Introductionmentioning
confidence: 99%
“…However, the storage materials are large numbers of particle aggregates, and their mechanical properties are extremely complex, which is difficult to reasonably estimate using the traditional classical mechanics theory and condensed matter physics theory 12 . In recent years, relevant scholars have found that the maximum dynamic pressure on the silo wall is often several times of the static pressure during silo discharging 13 16 . Thus, if the dynamic pressure on silo wall is not considered during the design process, it will lead to the instability of the silo.…”
Section: Introductionmentioning
confidence: 99%
“…However, the storage materials are large numbers of particle aggregates, and their mechanical properties are extremely complex, which is difficult to reasonably estimate using the traditional classical mechanics theory and condensed matter physics theory [12]. In recent years, relevant scholars have found that the maximum dynamic pressure on the silo wall is often several times of the static pressure during silo discharging [13][14][15][16]. Thus, if the dynamic pressure on silo wall is not considered during the design process, it will lead to the instability of the silo.…”
Section: Introductionmentioning
confidence: 99%